The data marketplace survey revisited - Florian Stahl; Fabian Schomm; Gottfried Vossen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2014)
Trading data as a commodity is increasingly popular. To get a better understanding of emerging data marketplaces, we have conducted two surveys to systematically gather and evaluate their characteristics. This paper is a continuation of a survey we conducted in 2012; it describes our findings from a second round done in 2013. Our study shows that the market is vivid with numerous exits and changes in its core business. We try to identify trends in this young field and explain them. Notably, there is a definite trend towards high quality data.
Keywords: 650; Data Market Places; Data Marketplaces Survey; Data Marketplaces Development